PRAKTIK JUAL BELI DI KAWASAN YANG DILARANG BERJUALAN OLEH PEMERINTAH DAERAH KABUPATEN SAMBAS DALAM PERSPEKTIF HUKUM ISLAM - Ibrahim, Ade (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
Buying and selling is the exchange of property on the basis of mutual willingness or transfer of property rights by obtaining other objects in exchange for the purpose of seeking profit (profit) based on the methods allowed in Islam. Buying and selling according to language is an absolute exchange. Work is one of the human activities to meet the needs of life. Islam also tells all people to work. In working, you should obey the applicable regulations in order to maintain security and order in the community. In fact, there are many traders who do not obey applicable regulations, such as Street Vendors (PKL) on Hasan Saleh street using sidewalks to sell, causing congestion and disturbing others around them. The Regional Government of Sambas Regency has regulated the issue of Street Vendors (PKL) in the Regional Regulation of Sambas Regency Number 7 of 2006 concerning